The study on tire tread depth measurement method based on machine vision. (April 2019) - Wang, Xi-Bo; Li, Ai-Juan; Ci, Qin-Peng; Shi, Meng; Jing, Tian-Long; Zhao, Wan-Zhong
The tire tread depth has strong influence on the braking performance of the vehicle and should be inspected periodically for driving safety. In order to determine the tire tread depth accurately and automatically, a tire tread depth measurement method based on machine vision was developed. During the measuring, a tire tread radial section image formed by a laser plane was captured when the tire rolls over the measuring device. Then, the image was calibrated to eliminate the lens distortion and processed to get the single-pixel center line. Consequently, the center line's pixel coordinates were transformed to world coordinates with the calibration information of the laser plane, and a profile curve of the tire radial section was obtained. Then, the tread grooves on the profile curve were identified and their positions are determined by an algorithm developed in this research. Finally, the depth of each groove was calculated successively. An experiment was conducted on a prototype system based on the measurement method developed in this article. The experimental result indicates that the measurement method can identify the tire tread groove and determine its position and measure its depth. The depth absolute error is less than 0.2 mm, which can meet the demand of tire tread depth measurement.